2018
DOI: 10.15835/nbha46211081
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Quality Assessment of Leaves and Stems of Fodder Ligneous Species

Abstract: The objective of this research was to investigate the effect of seasonality on the chemical composition and concentration of phenolic compounds in some ligneous species. The research was conducted at the Aristotle University’s farm, Thessaloniki, Greece. From five ligneous species (Robinia pseudoacacia var. monophylla, Amorpha fruticosa, Colutea arborescens, Morus alba and Arbutus unedo) samples (leaves and twigs) were collected during two different seasons (spring and autumn). All samples were analyzed for cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
1
2
2
Order By: Relevance
“…Özyılmaz (28) reported that TFW had 93.42% DM, 14.07% CP, 4.69% ash, 1.07% EE, 47.76% NDF and 40.93% ADF levels and that these values varied according to the organic or conventional cultivation of the tea plants and their harvest periods. Parissi et al (29) and Luginbuhl and Mueller (24) reported that R. pseudoacacia leaves had 27.3% CP (g/100g DM) and 28.0% (g/100g DM) respectively, which is consistent with the results of the present study.…”
Section: Resultssupporting
confidence: 93%
“…Özyılmaz (28) reported that TFW had 93.42% DM, 14.07% CP, 4.69% ash, 1.07% EE, 47.76% NDF and 40.93% ADF levels and that these values varied according to the organic or conventional cultivation of the tea plants and their harvest periods. Parissi et al (29) and Luginbuhl and Mueller (24) reported that R. pseudoacacia leaves had 27.3% CP (g/100g DM) and 28.0% (g/100g DM) respectively, which is consistent with the results of the present study.…”
Section: Resultssupporting
confidence: 93%
“…Crude protein is a key factor to discuss the quality of forage (Amiri, 2012), as mentioned in table 2, the protein content in A. unedo leaves (average value of 7.17 g/100 g of DW) was within the range of other works, which reported content of 7.2 and 6.8 g/100 g of DW (Tisserand & Faurie, 1994;Boubaker et al, 2004). However, a study conducted by Parissi et al (2018) showed higher protein content (10.8 g/100 g of DW) as compared to this study. Generally, it was reported that protein content in A. unedo leaves was found to exceed the required demands of small ruminants (Parissi et al, 2018).…”
Section: Nutritional Composition Of a Unedo Leavescontrasting
confidence: 87%
“…However, a study conducted by Parissi et al (2018) showed higher protein content (10.8 g/100 g of DW) as compared to this study. Generally, it was reported that protein content in A. unedo leaves was found to exceed the required demands of small ruminants (Parissi et al, 2018).…”
Section: Nutritional Composition Of a Unedo Leavescontrasting
confidence: 87%
See 1 more Smart Citation
“…The low total polyphenol content in this study may be explained by a combination of proportion of stem and leaves in the samples and seasonal fluctuations. Parissi et al (2018) found higher total polyphenol content in leaves than stems and lower content in autumn than spring for different browse species. However, our values were similar to those found by Rubanza et al (2006) and Mokoboki (2011) for Acacia spp.…”
Section: Discussionmentioning
confidence: 79%